Gerakan Seribu Hari Pertama Kehidupan Terhadap Sikap, Perilaku, Dan Tingkat Kemandirian Tindakan Pencegahan Kejadian Stunting: Movement for the First Thousand Days of Life on Attitudes, Behavior and Level of Independence, Actions to Prevent Stunting Events - Kamariyah, Nurul; Putri, Rahmadaniar Aditya; Setiyowati, Eppy; Afiyah, R. Khairiyatul (Chakra Brahmanda Lentera Institute, 2024)
Growth failure and discrepancy between height and age in childhood are the most common forms of malnutrition that can be seen globally, which will result in stunting. Stunting will hinder the development of human potential and resources throughout society because of its long-term impact on cognitive, affective and psychomotor functions. [1]. The incidence of stunting can be prevented by healthy living behavior from the time as a prospective bride, when the baby is in the womb, giving birth, postpartum and child care after birth until the golden period (under 2 years of age). The results of Kamariyah's research in 2023 in the working area of the Banyuurip Surabaya community health center with the results: it was still found that the majority of respondents in the research still had a poor level of knowledge, attitudes, behavior and level of independence in preventing stunting. As a form of research results, researchers continue these activities in the form of community service. The method used is to carry out mentoring movements to provide education and demonstrations in the first thousand days of life for pregnant women and mothers who have children aged before 2 years. The time used is one semester. The results achieved were an increase in knowledge, attitudes, behavior and level of independence to prevent stunting, almost all (90%) there was an increase in knowledge, almost all (92%) there was an increase in attitudes, and 96% there was an increase in behavior, and almost all (98%) ) there is an increase in the level of independence to prevent stunting. Descation: The first thousand days of life movement increases knowledge, attitudes, behavior and independence to prevent stunting. It is recommended that health workers provide community service.